Protein Phosphorylation in Parasites 2013
DOI: 10.1002/9783527675401.ch04
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosomatid Cell Division Kinases

Abstract: Advances have been made recently in understanding the order of events in the cell division cycles of Leishmania spp. and Trypanosoma cruzi, adding to previous knowledge of events in Trypanosoma brucei, and highlighting similarities and differences between these trypanosomatids. However, the present understanding of how the cell cycle is regulated by kinases still largely derives from analyses in T. brucei, since convenient genetic tools for analyzing the function of essential regulators -for example, inducible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 99 publications
(144 reference statements)
0
1
0
Order By: Relevance
“…Since T. brucei has been known to express essential kinases that are homologous to human kinases, we have found that repurposing human kinase inhibitors can be successfully utilized for uncovering antitrypanosomal lead compounds. …”
Section: Introductionmentioning
confidence: 99%
“…Since T. brucei has been known to express essential kinases that are homologous to human kinases, we have found that repurposing human kinase inhibitors can be successfully utilized for uncovering antitrypanosomal lead compounds. …”
Section: Introductionmentioning
confidence: 99%